PHYSICAL PROPERTIES OF ORAL LIQUID IN CHILDREN WITH MALOCCLUSION AND DIFFERENT ENAMEL RESISTANCE - N.I. Smolyar; M.Ju. Lesytskiy; T.Yu. Lysak (Український стоматологічний альманах, 2023)
One of the factors in the development of dental caries in children with malocclusion is the insufficient enamel mineralization in different age periods, that is, its resistance is reduced. An important role in the formation of enamel resistance is played by the oral fluid, in particular its physical properties, mineralization potential and protective mechanisms. Fluctuations in the pH of the oral fluid significantly depend on the hygienic condition of the oral cavity and the nature of the food. At the same time, the possibility of access of mineral elements to the surface of the enamel significantly worsens in case of increased viscosity and decreased rate of saliva secretion of oral fluid. This, in turn, contributes to the reduction of diffusion processes in tooth enamel and the creation of conditions for the development of enamel demineralization.